Insectos plagas defoliadores del cultivo de Tabaco (Nicotiana tobacum) en el Ecuador - Rivera Naranjo, Edwin Walberto (2022)
Tobacco also known by its scientific name (Nicotiana tabacum L) is a crop of the plant kingdom that is cultivated as an annual plant, it normally grows in moderate climates but over time it has been coupled to climate change, its stem is thin with few branches, it can grow up to two meters high and the length varies depending on the type of tobacco planted, it has a cluster of pink, reddish or white flowers, the fruit is an elliptical capsule with many small colored seeds. dark brown the root spreads depending on the soil and the technology used in cultivation. Tobacco, despite not being edible, is very profitable in our country, most of it is grown in the Guayas and the rest in the rivers, despite being profitable, tobacco growers have had to deal with defoliating insect pests, since these are not detected. in time they cause a big problem on the leaves. Tobacco is affected by defoliators that cause considerable losses in the yield and quality of the agricultural fruit. These insect pests generally feed on the soft leaves, but if they are not detected in time, they attack all the leaves, causing serious damage to the silver that They can even cause the death of it and lost in the production of tobacco. That is why we have to control the defoliated in time. The best control methods that are currently used are cultural control, common agricultural practices, biological control, use natural enemies, chemical control, the most common and used insecticides are Abamectin, Bacillus. thuringiensis var. Kurstaki that are sami-biological and the Methomyl.